Antibacterial and Anti‐Inflammatory Activity of Chitosan Film with Rhodomyrtus Tomentosa Leaf Extract Prepared Via 3D‐Printing Method - Quan Vo‐An; Chinh Thuy Nguyen; Uyen Thu Pham; Tuan Anh Nguyen; Duong Thanh Nguyen; Dung Tran Hoang; Lu Trong Le; Quyen Thi Cam Ngo; Hoang Thai (ChemistryOpen)
Abstract The combination of natural polymers and plant extract attracted much attention thanks to its valuable biological activities. This study presents the preparation and characterization of chitosan (CS) film containing Rhodomyrtus tomentosa leaf extract. In which, the Rhodomyrtus tomentosa leaf extract (SLE) with polyphenol‐rich fractions was extracted by an ultrasonic‐assisted extraction method. The prepared chitosan/polyphenol‐rich fractions film (CSPPF) was characterized using infrared (IR) spectroscopy, mechanical testing, scanning electron microscopy (SEM), and water absorption analysis. Antibacterial and anti‐inflammatory activities of the CSPPF were assessed using the agar well diffusion method and nitric oxide (NO) inhibition assays, respectively. Besides, the release of the extract from the CSPPF as well as the drug release kinetics was also tested. The Rhodomyrtus tomentosa leaf extract enhanced the antibacterial efficacy against Escherichia coli and enhanced the anti‐inflammatory activity as well as the swelling ability of the CSPPF. The CSPPF containing 1 wt.% of SLE can inhibit 77.70 % NO with an IC50 value of 19.40 μg/mL.